2015
DOI: 10.1007/s00276-015-1564-y
|View full text |Cite
|
Sign up to set email alerts
|

Coracobrachialis muscle: morphology, morphometry and gender differences

Abstract: The present study provides new evidence pertaining to the origin of CBM. Further, it was revealed that the predicted distance P of any upper extremity can be calculated by dividing the arm length by 5. Precise anatomical location of MCN in relation to CBM using unequivocal and well-defined anatomical landmarks will be imperative in modern surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 18 publications
2
47
0
Order By: Relevance
“…In addition to having its tendon shift in surgery for recurrent anterior dislocation of the shoulder, providing dynamic stabilisation of the glenohumeral joint, especially when the arm is in a vulnerable position of abduction and lateral rotation [1,6,7].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to having its tendon shift in surgery for recurrent anterior dislocation of the shoulder, providing dynamic stabilisation of the glenohumeral joint, especially when the arm is in a vulnerable position of abduction and lateral rotation [1,6,7].…”
Section: Discussionmentioning
confidence: 99%
“…It is inserted distally into the medial margin of the humeral shaft, between the distal insertions of the brachialis and triceps muscles. In a regular syntopy, the coracobrachialis muscle is pierced and innervated by the musculocutaneous nerve (MN) [9]; however, in some cases it has been reported that the MN does not pierce the coracobrachialis muscle [6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations